TiO2 nanotubes guided Pt nanorods growth via atomic layer deposition for mild photothermal antibacterial activity and enhanced fibroblast response - Liu, Huan; Zhang, Wangle; Xu, Boya; Cai, Dongxuan; Wang, Haochen; Chang, Xiaofeng; Zhou, Qin; Feng, Hao; Song, Wen; Li, Zhe (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSoft tissue integration (STI) and antibacterial capability are critical for the long-term success of dental implants. However, achieving both simultaneously remains a major clinical challenge. This study aims to address this challenge by developing a novel surface modification strategy that combines both robust antibacterial properties and favorable soft tissue responses for dental implants.MethodsA novel nanostructured coating was fabricated by embedding hollow platinum nanorods (PtNRs) into titania nanotubes (TNTs) using atomic layer deposition (ALD). The resulting PtNR@TNT platform was characterized to confirm its stable architecture and dual biofunctionality. Structural characterizations were conducted to verify that PtNRs were uniformly deposited along the inner walls of TNTs without compromising the nanotopography or hydrophilicity. Long-term in vitro degradation studies were performed to assess Pt retention and release. The antibacterial performance of the PtNR@TNT platform was evaluated under mild near-infrared (NIR) irradiation (0.5 W cm-2, 42 °C–45 °C) against S. aureus and P. gingivalis. Furthermore, human gingival fibroblasts (HGFs) were cultured on PtNR@TNT surfaces to study cell adhesion, proliferation, and migration. qPCR analysis was used to assess gene expression related to soft tissue responses.ResultsThe PtNR@TNT platform exhibited a stable structure with PtNRs uniformly distributed along the inner walls of TNTs, preserving the nanotopography and hydrophilicity. Long-term degradation studies demonstrated sustained Pt retention and minimal release of platinum (<50 μg L-1 over 12 weeks), indicating excellent safety. Under NIR irradiation, PtNR@TNT showed superior antibacterial activity, achieving over 99% bacterial reduction against S. aureus and P. gingivalis through a combination of photothermal and photodynamic effects. Additionally, HGFs demonstrated enhanced adhesion, proliferation, and migration on PtNR@TNT surfaces, with further promotion observed after NIR exposure. qPCR analysis revealed that NIR exposure upregulated the expression of key genes involved in soft tissue healing, including COL-1, FAK, ITGβ1, and VCL.DiscussionThe findings from this study suggest that the PtNR@TNT platform offers a promising surface modification strategy for dental implants. It combines robust antibacterial efficacy with favorable soft tissue responses under clinically safe photothermal conditions. The dual biofunctionalities, including enhanced antibacterial performance and improved soft tissue integration, make the PtNR@TNT platform a promising candidate for advancing dental implant technology.